Risk factors for incidental parathyroidectomy during thyroidectomy - Campos, Niklas Soederberg (2012)
Incidental parathyroidectomy is a common event in thyroid surgery. The literature shows a finding of parathyroid glands ranging from 6.4% to 31% in pathological specimens of the thyroid gland.Objective: To collect the amount of parathyroid glands found in surgical specimens of thyroidectomy and correlate with the histopathological and demographic variables.Methods: Retrospective study based on pathological reports of thyroidectomy from January 2007 to December 2008.Results: 442 patients were submitted to total thyroidectomy, and 2.93% had parathyroid glands, which corresponded to 13 of this total. The presence of papillary thyroid carcinoma associated with incidental parathyroidectomy was 10.11%, compared to the benign lesion: 1.4%.Conclusion: Papillary thyroid carcinoma was the variable associated with increased number of incidental parathyroidectomy.